Mixed-methods approach in evaluating safe abortion care services at public health facilities in North Shewa zone, central Ethiopia: a multicenter institutional cross-sectional study - Tamire, Aklilu; Birhanu, Bezawit; Negash, Abraham; Dechasa, Mesay; Masrie, Awoke; Shawel, Samrawit; Dereje, Jerman; Gebru, Tilaye; Kassa Tafesse, Obsan; Mengistu, Dechasa Adare; Sertsu, Addisu; Daka, Dawit Wolde (Frontiers in Health Services, 2024)
BackgroundOf the 55.7 million abortions that were performed globally, 25.1 million (45.1%) were not safe. Nearly 97% of these took place in developing countries. Approximately 71% of economically developed countries allow safe abortion care (SAC) services, whereas only 16% of developing countries permit it. In sub-Saharan Africa, 92% of mothers live in 43 countries where SAC services are restricted by law. Most Ethiopian women continue to self-terminate unwanted pregnancies in hazardous conditions. The aim of this evaluation was to assess input, care providers’ compliance with national guidelines, and clients’ satisfaction.MethodsA multicenter cross-sectional study design with a mixed-methods approach was used. Seven public health facilities were randomly selected where 75 health caseworkers were directly observed; 296 clients and 14 key informants were interviewed, respectively. A resource inventory checklist was used to assess all inputs. The overall SAC services evaluation was summarized from 40 indicators: 13 resource availability indicators, 14 healthcare workers' compliance to national guidelines indicators, and 13 clients' satisfaction toward SAC services indicators. A multivariate logistic regression model was fit to determine factors that affect client satisfaction at a p-value <0.005.ResultsThere were 75 healthcare providers in the maternal and child health departments in the study area. Except for the interruption of water and electricity, maternal waiting area, counseling, and procedural room, all are available making 94% of resources availability. All healthcare workers were compliant in providing anti-pain medication during procedures, identifying clients if they were targeted for an HIV/AIDS test, and providing their test results as per the guideline. Nevertheless, they were poorly compliant in respecting the clients (9, 12%) and taking vital sign (33, 44%). The overall compliance was 62.3%, while only 51% were satisfied with waiting time and privacy of counseling room. The overall client satisfaction was 65%. The overall evaluation of SAC services was 72.9%.ConclusionResource availability was excellent, which was in line with national SAC expectations while the healthcare workers’ compliance to national guidelines was fair, which deviated from expectations. The clients’ satisfaction and the overall evaluation were good, which was below the hypothesized expectation.